Synaptic connections of first‐stage visual neurons in the locust Schistocerca gregaria extend evolution of tetrad synapses back 200 million years. Issue 2 (25th October 2014) - Wernitznig, Stefan; Rind, Frances Claire; Pölt, Peter; Zankel, Armin; Pritz, Elisabeth; Kolb, Dagmar; Bock, Elisabeth; Leitinger, Gerd
ABSTRACT The small size of some insects, and the crystalline regularity of their eyes, have made them ideal for large‐scale reconstructions of visual circuits. In phylogenetically recent muscomorph flies, like Drosophila, precisely coordinated output to different motion‐processing pathways is delivered by photoreceptors (R cells), targeting four different postsynaptic cells at each synapse (tetrad). Tetrads were linked to the evolution of aerial agility. To reconstruct circuits for vision in the larger brain of a locust, a phylogenetically old, flying insect, we adapted serial block‐face scanning electron microscopy (SBEM). Locust lamina monopolar cells, L1 and L2, were the main targets of the R cell pathway, L1 and L2 each fed a different circuit, only L1 providing feedback onto R cells. Unexpectedly, 40% of all locust R cell synapses onto both L1 and L2 were tetrads, revealing the emergence of tetrads in an arthropod group present 200 million years before muscomorph flies appeared, coinciding with the early evolution of flight. J. Comp. Neurol. 523:298–312, 2015. © 2014 Wiley Periodicals, Inc.